Kualitas Produk, Promosi, dan Pelayanan terhadap Loyalitas Pelanggan pada Amanah Mart Sukoharjo - Annisa Rizki Septiandini (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the quality of the product, promotions, and service simultan ously and partly on customer loyalty at Amanah Mart Sukoharjo. This type of research is quantitative, the research population is all loyal customers who often shop at Amanah Mart Sukoharjo with the sampling technique using purposive sampling technique. Sample were taken by 100 respondents. Methods of data analysis using the classical assumption test, multiple linear regression analysis, hypothesis testing and test the coefficient of determination. The results showed that product quality, promotion and service had a simultaneous and significant effect on customer loyalty.